Readability of Patient Education Materials on the American Orthopaedic Society for Sports Medicine Website. Issue 4 (November 2014) - Eltorai, Adam E.M.; Han, Alex; Truntzer, Jeremy; Daniels, Alan H.
Abstract: Background: The recommended readability of patient education materials by the American Medical Association (AMA) and National Institutes of Health (NIH) should be no greater than a sixth-grade reading level. However, online resources may be too complex for some patients to understand, and poor health literacy predicts inferior health–related quality of life outcomes.Aim: This study evaluated whether the American Orthopaedic Society for Sports Medicine (AOSSM) website's patient education materials meet recommended readability guidelines for medical information. We hypothesized that the readability of these online materials would have a Flesch-Kincaid formula grade above the sixth grade.Methods: All 65 patient education entries of the AOSSM website were analyzed for grade level readability using the Flesch-Kincaid formula, a widely used and validated tool to evaluate the text reading level.Results: The average (standard deviation) readability of all 65 articles was grade level 10.03 (1.44); 64 articles had a readability score above the sixth-grade level, which is the maximum level recommended by the AMA and NIH. Mean readability of the articles exceeded this level by 4.03 grade levels (95% CI, 3.7–4.4; P < 0.0001). We found post-hoc that only 7 articles had a readability score ≤ an eighth-grade level, the average reading level of US adults. Mean readability of the articles exceeded this level by 2.03 grade levels (95% CI, 1.7–2.4; P < 0.0001).Conclusion: The readability of online AOSSM patient education materials exceeds the readability level recommended by the AMA and NIH, and is above the average reading level of the majority of US adults. This online information may be of limited utility to most patients due to a lack of comprehension. Our study provides a clear example of the need to improve the readability of specific education material in order to maximize the efficacy of multimedia sources.